Who could that be at this hour? - Snicket, Lemony. (All the wrong questions ;, 2012)
Thirteen-year-old Lemony Snicket begins his apprenticeship with S. Theodora Markson of the secretive V.F.D. in the tiny dot of a town called Stain'd By The Sea, where he helps investigate the theft of a statue.